Kajian Ekopuitika Dalam Pantun Nasihat Karya Anwarsani - Misnawati Misnawati; Wihadi Admojo; Diplan Diplan; Siti Rahmawati; Nabila Salwa (FKIP Universitas Palangka Raya, 2023)
The aims of the research are (1) to describe the structure of the pantun in Anwarsani's work identified based on elements such as lines, arrays, rhymes, and stanzas. (2) Describe the style of language used by Anwarsani in his rhymes. (3) Describe the ecological messages contained in Anwarsani's poems of advice, and how the meanings related to concern for the environment, nature conservation, and the importance of maintaining ecosystem harmony are interpreted. This study uses a qualitative approach to describe the structure of the pantun, language style, ecological messages, and eco-poetic significance in Anwarsani's work. This approach allows researchers to understand in depth the characteristics and meaning contained in the rhymes. The research data is in the form of Anwarsani's poems of advice which are analyzed using the text analysis method. Through reading and identifying pantun structures, observing language styles, and extracting ecological messages, researchers can gain a comprehensive understanding of the elements studied.